Uso da inteligência artificial no poder judiciário brasileiro: aspectos e análise da comunicação estratégica do tribunal de justiça de Pernambuco. - Calado, Matheus Lopes (2024)
The advancement of Artificial Intelligence (AI) is an undeniable reality and is increasingly present in all sectors of society, both in the private and public spheres. In Brazil, this progress is noticeable not only in private companies and institutions, but also in regional courts and the Superior Court. These advancements are observed closely, as they are directly related to the fundamental principles of justice, such as transparency, impartiality, and efficiency. Additionally, clear and strategic communication with society about the use of artificial intelligence is essential. It is necessary to ensure that the population understands the benefits and challenges that AI brings to the judicial system and society as a whole. Transparent and accessible communication helps promote trust in the judiciary and ensures informed and engaged participation of society in discussions about the use of AI. The advancement of artificial intelligence in the Brazilian judicial system is evident and requires a careful and transparent approach. Strategic communication plays a fundamental role in this process, ensuring that the fundamental principles of justice are preserved and that society is informed and involved in the transformations provided by AI.